Hak-Hak Tersangka Pada Tingkat Penyidikan - Luil Maknun (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2023)
The law is a norm that contains rules and provisions that guarantee the rights and obligations of individuals and societies. The existence of the law is intended to create harmony of life among societies, nations and nations. This research uses normative methods. The legal protection of the right of the suspect to criminal investigation. The right of priority to the settlement of cases, the right to preparation of defence, the rights to testify freely, the Right to obtain a linguist, the Rights to legal assistance and relating to detention, The Rights to be informed, to contact or receive family visits, The right to appoint a witness de charge and expert witnesses. The legal role is necessary in regulating the distribution of power and authority and its implementation among the various state institutions and tools of state supplies so that the management of state life can be carried out in an orderly and orderly manner, as well as in carrying out the vitalization and functionalization of existing norms and positive values.